2005
DOI: 10.1002/bip.20429
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water on the glass transition of human hair

Abstract: The glass transition of human hair and its dependence on water content were determined by means of differential scanning calorimetry (DSC). The relationship between the data is suitably described by the Fox equation, yielding for human hair a glass transition temperature of T(g) = 144 degrees C, which is substantially lower than that for wool (174 degrees C). This effect is attributed to a higher fraction of hydrophobic proteins in the matrix of human hair, which acts as an internal plasticizer. The applicabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 89 publications
3
63
0
2
Order By: Relevance
“…5 For a soluble protein, this process is claimed to be a reversible, one-step, first-order transition. 8,9 However, in practice, even in complex heating and cooling programs, as implemented in the context of another investigation, 10 no indication was found that the denaturation process for the insoluble hair keratin may be to any extent reversible, showing the primacy of kinetic control over the process, 9 which is exerted by the matrix surrounding the IFs. 5 The baseline for the DSC curves is generally a fairly straight line, indicating that there are no other major processes present.…”
Section: Discussionmentioning
confidence: 97%
“…5 For a soluble protein, this process is claimed to be a reversible, one-step, first-order transition. 8,9 However, in practice, even in complex heating and cooling programs, as implemented in the context of another investigation, 10 no indication was found that the denaturation process for the insoluble hair keratin may be to any extent reversible, showing the primacy of kinetic control over the process, 9 which is exerted by the matrix surrounding the IFs. 5 The baseline for the DSC curves is generally a fairly straight line, indicating that there are no other major processes present.…”
Section: Discussionmentioning
confidence: 97%
“…Several of the authors who researched the thermal analysis applied on human hair executed TG and DSC analyses with the purpose of characterizing the keratin of human hair [54][55][56] and verifying the effects of hair care products on keratin structure [15,57,58].…”
Section: Thermal Analysismentioning
confidence: 99%
“…6 The water content in the dried hair was minimized (4.5% by weight). 6 A lock of 100 hairs (33 mm, 19.021.0 mg) was bundled up with a copper film (3.0 © 8.0 © 0.1 mm 3 ) and was degassed in vacuo.…”
mentioning
confidence: 99%
“…6 The water content in the dried hair was minimized (4.5% by weight). 6 A lock of 100 hairs (33 mm, 19.021.0 mg) was bundled up with a copper film (3.0 © 8.0 © 0.1 mm 3 ) and was degassed in vacuo. The sample was then sealed in an ESR quartz cell under dry helium atmosphere and was exposed to near-UV radiation at 77 K. 5 A Xe-lamp (UVF-203S, Sanei Electric, wavelength; 255 to 390 nm, 0.78 W cm…”
mentioning
confidence: 99%
See 1 more Smart Citation